2014
DOI: 10.1111/ahg.12071
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood Ratio Tests in Rare Variant Detection for Continuous Phenotypes

Abstract: SummaryIt is believed that rare variants play an important role in human phenotypes; however, the detection of rare variants is extremely challenging due to their very low minor allele frequency. In this paper, the likelihood ratio test (LRT) and restricted likelihood ratio test (ReLRT) are proposed to test the association of rare variants based on the linear mixed effects model, where a group of rare variants are treated as random effects. Like the sequence kernel association test (SKAT), a state-of-the-art m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 48 publications
5
27
0
Order By: Relevance
“…These results are consistent with those reported by Zeng et al [53] and by Lippert et al [30], who found the LRT to be generally more powerful than the score test across their simulated settings. Although Lippert et al did not consider the behavior of the two tests under misspecified weights, they reported the same pattern of results in real data analysis, where the LRT yielded consistently more associations than the score test.…”
Section: Resultssupporting
confidence: 92%
“…These results are consistent with those reported by Zeng et al [53] and by Lippert et al [30], who found the LRT to be generally more powerful than the score test across their simulated settings. Although Lippert et al did not consider the behavior of the two tests under misspecified weights, they reported the same pattern of results in real data analysis, where the LRT yielded consistently more associations than the score test.…”
Section: Resultssupporting
confidence: 92%
“…In the bootstrap ReLRT algorithm, B was set to 2000, and for the approximation mixture in we selected L = 2000, 1500, 1000, 800, 500, 300 and 100. We also implemented the simulation-based algorithm for the finite sample null distribution of ReLRT [ 20 , 35 , 36 ], and the number of runs in this algorithm is set to 10000. Besides ReLRT, the burden test, the optimal SKAT (SKAT-O) [ 37 , 38 ], SKAT [ 12 ], the genetic random field (GenRF) model [ 39 , 40 ] and the mixed effects score test (MiST) [ 41 ] were conducted together for comparisons.…”
Section: Settings Of Numerical Studymentioning
confidence: 99%
“…For example, it is well known that single nucleotide polymorphisms (SNPs) can be divided into groups in terms of functional annotations or genes, and genes in turn can be grouped into pathways due to the shared biological function. It has been shown that incorporating such useful group/functional information into model fitting can substantially boost statistical power in genetic association studies and can facilitate our understanding of the genetic architecture of disease variation by heritability partition [25][26][27][28][29][30][31][32][33]. One widely-used group source is the pathway information in the Kyoto Encyclopedia of Genes and Genomes (KEGG) [34,35], which integrates information on genomic, chemical and system functions and groups genes with highly related sequences by analyzing the sequence similarity of genes.…”
Section: Introductionmentioning
confidence: 99%